Late Onset Deformity in a Healed Fracture: A Case of Paediatric Post Traumatic Tibia Valga - Sakinah M. Razali; Mohd Hilmi N,; Nur Dina A; Abu’ Ubaidah Amir N; Mohd Asha'ari Bain (USIM Press, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 9 Issue 2 Page (87-89)